BBC Proms 2015: Gary Carpenter, Anders Hillborg, Ørjan Matre, Alissa Firsova, B Tommy Andersson. (7th December 2015) - Broad, Leah
Abstract : Sibelius' and Nielsen's 150th anniversary year has prompted a proliferation of events to celebrate the music of the Nordic composers, from conferences to concert series. The Proms has been no exception, with an unusually high number of Nordic composers represented throughout the festival (although Glazunov, also in his 150th anniversary year, has been forgotten). British composer Gary Carpenter's Dadaville was premiered on the first night, which opened to the sounds of Nielsen's Maskarade and Sibelius's Belshazzar's Feast, while later concerts covered here presented premieres by the Swedish composers Anders Hillborg and B Tommy Andersson, the Norwegian composer Ørjan Matre, and Moscow-born (though UK-based) composer Alissa Firsova.